(untitled) (Medicine Today, 2018)
Lichen Myxedematosus (LM) is an uncommon and distinct disease entity characterized by cutaneous mucin deposition in dermis. It is classified in several subtypes depending on many factors including the monoclonal gammapathy, pattern of skin involvement and systemic involvement. We now present a case of LM which is localized in respect of skin involvement but according to recent classification it falls into a diagnosis of ’atypical localized not well- specified cases’. This is a very rare case and to the best of our knowledge, it is the first case report in medical literature until now. We treated the case with a short course of oral Prednisolone and got excellent result. Patient has been followed up in every 6 month for last 13 yrs and observed no progression to scleromyxedema. Medicine Today 2018 Vol.30(1): 44-46